2005
DOI: 10.1186/1471-227x-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Early tracheostomy in closed head injuries: experience at a tertiary center in a developing country – a prospective study

Abstract: Background: An important factor contributing to the high mortality in patients with severe head trauma is cerebral hypoxia. The mechanical ventilation helps both by reduction in the intracranial pressure and hypoxia. Ventilatory support is also required in these patients because of patient's inability to protect the airway, persistence of excessive secretions, and inadequacy of spontaneous ventilation. Prolonged endotracheal intubation is however associated with trauma to the larynx, trachea, and patient disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 20 publications
0
18
0
2
Order By: Relevance
“…17,28,48,59,63 Some authors have suggested that early tracheostomy decreases ICU mortality rate 23,64,65 and overall in-hospital mortality, 26,66 whereas other studies have reported a mortality rate reduction on a long-term basis, but not on a shortterm basis. 41,55,67 And finally, these observations were not confirmed by other authors who could not demonstrate any significant association between timing of tracheostomy and reduction of mortality rate following surgery, polytrauma, and severe head injury. 19,40,[68][69][70][71] The benefits of early tracheostomy for patients who require extended periods of MV, compared to prolonged translaryngeal intubation have been debated.…”
Section: Discussionmentioning
confidence: 77%
“…17,28,48,59,63 Some authors have suggested that early tracheostomy decreases ICU mortality rate 23,64,65 and overall in-hospital mortality, 26,66 whereas other studies have reported a mortality rate reduction on a long-term basis, but not on a shortterm basis. 41,55,67 And finally, these observations were not confirmed by other authors who could not demonstrate any significant association between timing of tracheostomy and reduction of mortality rate following surgery, polytrauma, and severe head injury. 19,40,[68][69][70][71] The benefits of early tracheostomy for patients who require extended periods of MV, compared to prolonged translaryngeal intubation have been debated.…”
Section: Discussionmentioning
confidence: 77%
“…Yet, overall rates of pneumonia and mortality were not different between the two groups. On the other hand, in a small prospective study, Chintamani et al found fewer intubation associated complications and improved mortality in patients receiving early tracheostomy as compared to prolonged mechanical ventilation [39]. Despite these multiple studies there remains no consensus to guide timing of tracheostomy these critically ill patients [14,40,41].…”
Section: Discussionmentioning
confidence: 98%
“…For example, trauma patients with significant head or neck injuries often require tracheostomy for prolonged airway maintenance regardless of whether there is concomitant respiratory failure. This may facilitate the decision for tracheostomy placement earlier in the hospital course [30] and may also result in decreased duration of mechanical ventilation and faster recovery in this subpopulation [14,15]. In contrast, it is more difficult to predict the need for tracheostomy in trauma patients with prolonged respiratory failure without significant head or neck injuries.…”
Section: Introductionmentioning
confidence: 90%